CO2-capture and geological storage as a climate policy option: Technologies, concepts, perspectives - Manfred Fischedick (Wuppertal Institut für Klima, Umwelt, Energie, 2007)
The idea of removing carbon dioxide from flue gas and industrial gas flows and putting it into suitable long-term storage sites is referred to as Carbon Capture and Storage (CCS). This publication provides a close look at this new line of technologies, describing its current status and outlining the prospects for development. The approach is both diagnostic and analytical, identifying the questions a technology assessment poses and showing the steps that need to be taken to implement CCS. CCS is currently moving to the centre of climate policy discussion. Nonetheless this line of technologies is still the subject of controversial discussion. On the one hand there is a clear hope that these technologies will open up opportunities to use fossil fuels without harming the climate and thus make it possible to continue using oil, natural gas and above all coal even under a stricter climate regime. Accordingly, numerous R&D projects have been initiated all over the world, and various demonstration projects are at the planning or implementation stage. On the other hand, CCS (especially the storage part) has given rise to considerable scepticism from an ecological point of view. – – Die vorliegende Broschüre setzt sich mit der Technologie der CO2-Abtrennung und Speicherung (CCS: Carbon Capture and Storage) auseinander. Sie bereitet den heute verfügbaren Sachstand auf und beschreibt die Entwicklungsperspektiven und Potenziale. Sie geht dabei sowohl diagnostisch als auch analytisch vor und zeigt die noch offenen Fragen für die Bewertung dieser Technologielinie sowie die noch notwendigen Handlungsschritte für ihre Umsetzung auf.
urn:nbn:de:101:1-200910201659
Keywords: 620